Gnathic Bones and Hyperparathyroidism: A Review on the Metabolic Bony Changes Affecting the Mandible and Maxilla in case of Hyperparathyroidism. (9th July 2020) - Ibrahem, Hazim Mahmoud
Abstract : Parathyroid glands secrete the parathyroid hormone that plays an essential role in bone remodeling. Excessive production of parathyroid hormone causes a common metabolic bone disorder known as hyperparathyroidism that is classified into primary, secondary, or tertiary. In hyperparathyroidism, the late bony complication is manifested as a giant cell osteolytic lesion called "brown tumor." Primary hyperparathyroidism is usually a sporadic disorder, but in minority of cases it occurs in inherited forms, and one of these forms is the hyperparathyroidism-jaw tumor syndrome, which is characterized by primary hyperparathyroidism and ossifying fibroma in the mandible and/or maxilla.